Analisis Metode Penerjemahan dalam Novel “Alice’s Adventures in Wonderland” - Sari, Luthfiana Widya; Dewi, Ika Sari (JURNAL PENDIDIKAN & PENGAJARAN (JUPE2), 2024)
Comparing the translation of literary works and the translation of scientific texts shows the differences in terms of complexity and challenges. One example of a literary work is a novel. Novels with figurative language and idiomatic expressions certainly need to be translated accurately for the target readers. This study aims to explain the translation methods used in Alice's Adventures in Wonderland. This research is a descriptive qualitative research. The data sources in this study are taken from the original English novel published by D. Appleton and Co in 1866 and the Indonesian translation translated by Inkraian in 2015 published through wattpad. The research was conducted using the translation method proposed by Newmark (1998). The results show that there are seven translation methods used in translating Alice's Adventures in Wonderland, namely 6 data for literal translation, 6 data for free translation, 5 data for faithful translation, 4 data for communicative translation, 4 data for adaptation translation, 3 data for semantic translation, and 2 data for idiomatic translation.